Willis-Ekbom disease is not associated with poor cardiovascular health in adults. Issue 1 (December 2015) - Dredla, Brynn; Del Brutto, Oscar; Lee, Augustine; Castillo, Pablo
Abstract Background Willis-Ekbom disease (WED), also calledrestless legs syndrome (RLS), is a neurologic sensorimotor disease that may be associated with cardiovascular disease. Given high morbidity and mortality rates of cardiovascular disease worldwide, we assessed the relation between WED/RLS and cardiovascular health risks in a native South American population. We prospectively analyzed data from The Atahualpa Project of Ecuadorian adults aged 40 years and older. Physicians interviewed consented persons on the health behavior and health factors of the American Heart Association (AHA) for ideal cardiovascular health in adults and underwent fasting laboratory blood collection and blood pressure evaluation. Certified neurologists conducted face-to-face interviews using the International Restless Legs Syndrome Study Group (IRLSSG) field instrument. Persons testing positive for WED/RLS and age-and sex-matched controls underwent confirmatory physical examinations conducted by a neurologist and a sleep specialist to whom IRLSSG designation was blinded. Findings Of 665 persons, 94 (14 %) tested positive in IRLSSG; 40 (6 %) had a diagnosis of WED/RLS after neurologic examination and interview. Patients with WED/RLS were younger (53.5 vs 59.9 years, P  = .001), without significant differences in sex ratios. Among AHA risk factors, only obesity was significantly more prevalent among patients with WED/RLS (42.5 % vs 23.5 %, P  = .01). However, after adjustment for confounders, body mass index was not significantly associated with WED/RLS. Conclusions In adult Amerindians, although obesity and body mass index were associated with WED/RLS on univariate analyses, the association was not present after adjustment for confounders. No other significant associations were found between WED/RLS and AHA cardiovascular metrics.